The Effectiveness Of Focus Group Discussions (Collaborative Learning Techniques) To Teach English Is Viewed From The Students' Motivation (Conference on English Language Teaching, 2024)
The objectives of the research are;(1) to Analyse whether FGD Collaborative Learning Technique is more effective than cooperative Learning Technique in teaching English skill for the sixth semester students of Tarbiyah of UIN Prof. K.H. Saifuddin Zuhri Purwokerto in the academic year of 2023/2024, (2) to analyse whether the English skill of the students having high motivation is better than that of those having low motivation; and (3) to analyse whether there is an interaction between teaching technique and motivation in teaching English for the sixth semester students of Tarbiyah of UIN Prof. K.H Saifuddin Zuhri Purwokerto. The technique that was applied in this research was an experimental study. It was conducted at Tarbiyah by UIN Prof. K.H. Saifuddin Zuhri Purwokerto in the academic year 2023-2024. The population of the research is the sixth semester of Tarbiyah at UIN, Prof. K.H. Saifuddin Zuhri Purwokerto, in the academic year 2023-2024. The samples were divided into two classes. In taking the sample, the cluster random sampling technique was used. Each class was divided into two groups (the students who have high motivation and the students who have the students who have low motivation). The researcher obtained quantitative data. They are the students ‘scores on the’ English test after having eight times of treatment for each class. The researcher analyzed the data using ANOVA and the Turkey test. Based on the results of the data analysis, the research findings are: (1) the FGD collaborative learning technique is more effective than the cooperative learning technique to teach English for the sixth semester of UIN Prof. K.H. Saifuddin Zuhri Purwokerto; (2) the English skill achievement of the students with high motivation is better than that of those with low motivation; and (3) there is an interaction between teaching technique and motivation. Based on these research findings, it can be concluded that FGD Collaborative Learning Technique is an effective technique to teach English in the sixth semester of UIN Prof. K.H. Saifuddin Zuhri Purwokerto.